Elity polityczne w Związku Radzieckim - Żyromski, Marek (Wydział Prawa i Administracji UAM, 1992)
Soviet leaders exerted great influence not only on the functioning of social order but also on the functioning of elites and on the mechanisms of selection of member of elites. However, the sociological theory of elites neglects the role of on individual in the elite, lmiting itself to the level of mafia, clique or a similar group. The sociological theory of elits, with its roots in the analysis of parliamentary democracy, may also be applied to analysing totalitarian systems.
Political elites in the Soviet Union